Students’ Metacognitive Awareness and Its Impact on Writing Skill - Ramadhanti, Dina; Yanda, Diyan Permata (Universitas Negeri Makassar, 2021)
One of the factors that can affect the ability to write explanatory text is metacognitive awareness. By using the descriptive method, the students' level of metacognitive awareness was explained, and by using the correlational method the effect of metacognitive awareness towards explanatory text writing ability was explained. The results showed that as many as 25 students had a high level of awareness while 38 others had a moderate level of awareness. The relationship between metacognitive awareness variables and the ability to write explanatory text is significant and very strong seen from the range of correlation values, namely 0.812. Metacognitive awareness affects the ability to write explanatory text by 66% and the remaining 44% is influenced by other factors. This shows that metacognitive awareness has an important role in writing. Students must always increase their metacognitive awareness. Efforts that can be made to raise students' metacognitive awareness are that lecturers carry out writing learning with a cognitive process approach to increase metacognitive knowledge and apply metacognitive strategies so that students have metacognitive skills to complete writing assignments.